The Application Of Distributor Responsibility In Transboundary Haze Pollution Cases In Riau Based On Distrubutive Justice And Ethics - Indrasari, Febrina (Universitas Negeri Gorontalo, 2023)
Forest and land fires not only cause losses to the country of origin where the fire occurred, but also have an impact on other countries in the form of transboundary smoke pollution. The occurrence of transboundary smoke pollution that causes disruption to the environment of other countries is an act that is contrary to the principles of international law, especially those governing international environmental law. This research examines the worst forest and land fires that occurred in Riau. This research uses a doctrinal approach with consideration of research targets in the form of laws and regulations by examining the accuracy of arrangements, relations between norms and testing the norm system. The research approach analyzes legal theory, jurisprudence, and legal philosophy, and does not avoid the use of certain facts as support in research analysis. In this approach, the author analyzes the distributor's responsibility in the case of transboundary haze pollution in Riau. The result is that the parties responsible in the case of transboundary air pollution or Transboundary Haze Pollution in addition to the polluter, namely palm oil companies in Riau, also involve the state, in this case the Indonesian government as the party authorized to grant licenses and supervise the business licenses that have been issued, as well as being responsible as a contributor, namely the state of Singapore because of its financing to companies that cause air pollution in Riau. As well as making financiers, namely banks, one of the distributors in cross-border pollution in accordance with the polluter pays principle, which is the main principle that the polluter must be the payer.